PERILAKU IRRASIONAL KONSUMEN PENGGUNA E-COMMERCE IRRASIONAL BEHAVIOURAL OF E-COMMERCE CONSUMER - Rahmidilla, Sri; Luthfie, Muhammad; Agustini, Mrs. (Universitas Djuanda Bogor, 2019)
Nowdays, society mindset have been develpoed, the developing of technology and communications along with high spirit and creativity have been motivate for anew market with modern concept. One of it is e-commerce. The approach of this study is the qualitative approach and using difusi inovation theory. While the populations is consumer who use e- commerce. The result of this study is irrasional consumer who used e-commerce to fulfil everyday needed, consumer not jut uses smartphone as enterntainment but also as a shopping places and works.Keywords: E-commerce, consumer behavioural, Irrasional.